2015
DOI: 10.1111/ijfs.12807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano‐TiO2LDPE packaging on microbiological and physicochemical quality of Pacific white shrimp during chilled storage

Abstract: Summary Nano‐TiO2‐modified low‐density polyethylene (NTLDPE) packaging was prepared by blending LDPE with nano‐TiO2. The effects of NTLDPE packaging on quality of Pacific white shrimp during storage at 4 °C were investigated. Results showed that NTLDPE lowered the K value by 28.50%, while increased sensory score by 30.77% in comparison with the control. NTLDPE packaging retarded the decrease of whiteness and water holding capacity and the increase of melanosis score based on the signs of freshness and deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 43 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Reagents Distilled water, acetic acid, ethanol, nitric acid and 30% hydrogen peroxide, used as food simulants were purchased from Chinese Medicine Group Chemical, Reagent Co., Ltd, China. Luo et al (2015), Nano-TiO 2 or nano-ZnO particles were modified using the titanate crosslink reagent NDZ-201 (Dao Ning Ltd., Nanjing, China), before mixed with LDPE for 10 min in a high-speed mixer (SHR-10A, SHIHUYUE Ltd., China). Next, the mixture was extruded by a twin-screw extruder (HAAKE Polylab OS; Thermo Electron GmbH Ltd., Ulm, Germany) at 180℃ after cooling, then cut into granules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reagents Distilled water, acetic acid, ethanol, nitric acid and 30% hydrogen peroxide, used as food simulants were purchased from Chinese Medicine Group Chemical, Reagent Co., Ltd, China. Luo et al (2015), Nano-TiO 2 or nano-ZnO particles were modified using the titanate crosslink reagent NDZ-201 (Dao Ning Ltd., Nanjing, China), before mixed with LDPE for 10 min in a high-speed mixer (SHR-10A, SHIHUYUE Ltd., China). Next, the mixture was extruded by a twin-screw extruder (HAAKE Polylab OS; Thermo Electron GmbH Ltd., Ulm, Germany) at 180℃ after cooling, then cut into granules.…”
Section: Methodsmentioning
confidence: 99%
“…Several food package materials, containing NPs, have been investigated for their anti-microbial and anti-photochemical properties, which were greatly involved in food and cosmetic packaging (Marcous et al, 2017;Bieberstein et al, 2013). Luo et al (2014Luo et al ( & 2015 have proved the excellent properties of nano-TiO 2 modified LDPE on suppressing microbiological and physicochemical decay of shrimp and strawberry packaging. Nano-TiO 2 was often applied in packaging as a photo catalytic antibacterial agent (Xing et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that suspensions of ZnO were effective against all the strains; furthermore, ZnO nanoparticles diminished initial growth when these species were inoculated in sheep meat. Silica nanoparticles (nano-SiO 2, NSLDPE) (Luo et al, 2015a) and titanium nanoparticles (nano-TiO 2, NTLDPE) (Luo et al, 2015b) were blended with low-density polyethylene (LDPE) to produce packaging (NSLDPE and NTLDPE, respectively) that was shown to be a promising alternative preservation process for shrimp preservation during chilled storage. These authors found that Pacific white shrimp packaged with NTLDPE or NSLDPE preserved freshness by reducing the total viable count, the total volatile base nitrogen (TVB-N) contents, thiobarbituric acid reactive substances (TBARS), and ATP degradation (K value) compared to the control (LDPE).…”
Section: Non-encapsulating Nanoparticlesmentioning
confidence: 99%
“…The nano-TiO 2 -low density polyethylene (LDPE) packaging showed promising results in maintaining the quality and shelf life of Pacific white shrimp [130]. The TiO 2 -LDPE nanocomposite material inhibited the growth of spoilage bacteria and lowered the polyphenol oxidase (PPO) activity.…”
Section: Food Packaging and Antimicrobial Actionsmentioning
confidence: 99%